The Effectiveness of Maritim-Based Physics Teaching in Increasing The Science Process Skills of SMA Negeri 2 Dumai Students - Indri Widyastuti; Muhammad Sahal (Science Education Department of Mathematics and Natural Sciences Education Faculty of Teacher Training and Education, Universitas Riau in collaboration with the Association of Indonesian Science Educators (PPII), 2023)
Because they allow for the use of the scientific method in performing inquiries and are anticipated to be able to pick up new information, science process skills are crucial for pupils. This study's goal was to explain how well students could apply their knowledge of marine environmental physics to static fluid content for class XI SMA Negeri 2 Dumai. This kind of study uses a non-equivalent posttest only control group design in a quasi-experimental setting. All 288 students in class XI at SMA Negeri 2 Dumai were included in the population. To identify the populace, a simple random sampling technique is employed. The experimental group's posttest mean score for scientific process skills (M = 61.80, SD=11.92) is greater than the control group's posttest mean score for those same skills (M = 50.35, SD=13.63). According to the findings, classes using marine contextual learning have better pupil scientific process skills than classes using traditional learning. When viewed from a gender viewpoint, there is no clear variation between the science process skills of male and female students.